Double-Crop Sunflower Cost-Return Budget in Central and Kansas - Dumler, Troy J.; Duncan, Stewart R. (My University, 2006)
This publication provides estimated cost and returns for forward farm planning for a double-crop sunflower production system in central and eastern Kansas.
MF2145_2006_10
Keywords: MF2145; Crops; Economics; MF